Fredholm one-dimensional boundary-value problems with parameter in Sobolev spaces - Atlasiuk, O. M.; Mikhailets, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
For systems of linear differential equations on a compact interval, we investigate the dependence on a parameter $ε$ of thesolutions to boundary-value problems in the Sobolev spaces $W^n_{∞}$. We obtain a constructive criterion of the continuousdependence of the solutions of these problems on the parameter $ε$ for $ε = 0$. The degree of convergence of these solutionsis established.